The Importance of Students’ Motivation for Their Academic Achievement – Replicating and Extending Previous Findings - Steinmayr, Ricarda; Weidinger, Anne F.; Schwinger, Malte; Spinath, Birgit (Frontiers in Psychology, 2019)
Achievement motivation is not a single construct but rather subsumes a variety of different constructs like ability self-concepts, task values, goals, and achievement motives. The few existing studies that investigated diverse motivational constructs as predictors of school students’ academic achievement above and beyond students’ cognitive abilities and prior achievement showed that most motivational constructs predicted academic achievement beyond intelligence and that students’ ability self-concepts and task values are more powerful in predicting their achievement than goals and achievement motives. A flaw of these previous studies is that they did not assess all motivational constructs at the same level of specificity as the achievement criteria (e.g., hope for success in general was compared to mathematical ability self-concept when predicting math grades). In line with the Brunswik symmetry principle, correlations greatly vary depending on the constructs’ level of specificity considered in the analysis. Thus, it is not resolved yet whether some motivational constructs, e.g. ability self-concept, turned out to be better predictors of domain specific grades in comparison to other motivational constructs, e.g. general achievement motives, due to their higher criterion validity or due to the matched specificity of predictor and criterion. The aim of the present study was to investigate whether the reported previous findings can be replicated when ability self-concepts, valuestask values, goals, and achievement motives are all assessed at the same level of specificity as the achievement criteria (e.g., hope for success in math and math grades). The sample comprised 345 11th and 12th grade students (M = 17.48 years old, SD = 1.06) from the highest academic track (Gymnasium). Students self-reported their ability self-concepts, task values, goal orientations, and achievement motives in math, German, and school in general. Additionally, we assessed their intelligence and their current and prior GPA and grades in math and German. Relative weight analyses revealed that domain-specific ability self-concept, motives, valuestask values and learning goals but not performance goals explained a significant amount of variance in grades above all other predictors of which ability self-concept was the strongest predictor. Results are discussed regarding their implications for investigating motivational constructs with different theoretical foundation.